Buoyancy affects stranding rate and dispersal distance of floating litter entering the sea from river mouths. (December 2021) - Maclean, Kyle; Weideman, Eleanor A.; Perold, Vonica; Ryan, Peter G.
Abstract: Rivers are a major source of litter entering the sea but our understanding of the transport and fate of plastics in estuarine environments is poor. Marked blocks of varying buoyancy were released at three river mouths in South Africa. Of the 1400 blocks released, 80% were recovered on nearby beaches, with a higher recovery rate for more buoyant blocks. Dispersal distances increased with decreasing buoyancy at all sites; median dispersal distance of stranded items ranged from 20 to 90 m for expanded polystyrene (EPS) to 70–90 m for wood and 60–1042 m for high density polyethylene (HDPE) blocks. Floating litter in estuaries is subject to bidirectional flow and export is largely controlled by hydrodynamic conditions such as tides, winds, and wave action, as well as coastal structure and vegetation. Cleaning beaches around river mouths will help to reduce leakage of plastic and other litter into the sea. Highlights: Most floating litter washes ashore rather than dispersing out to sea. Tides, winds and currents all affect stranding rates and dispersal distances. The structure of the coast and associated waves are crucial. Some litter items move from the sea into estuaries.